Case reportImmunosuppressive therapy induced coronary vasospasm and acute myocardial infarction in a patient undergoing new renal transplantation - Biyik, Ismail; Akturk, Ibrahim Faruk; Yalcin, Ahmet Arif; Celik, Omer; Oner, Ender (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Immunosuppressant agents such as calcineurin inhibitors (CNI) used after solid organ transplantation may cause endothelial dysfunction, and coronary and renal arterial vasospasm. We report a patient presenting acute ST segment elevation myocardial infarction (STEMI) at the second week of renal transplantation. In the case of STEMI in patients with solid organ transplants under immunosuppressive therapy with CNI, coronary vasospasm associated with these drugs should be kept in mind before starting any interventional procedure. High dose nitroglycerine may immediately resolve tacrolimus or cyclosporine A induced coronary vasospasm. Calcium channel blockers should immediately be added to treatment because of the short half-life of nitroglycerine.